Factores de riesgo para el desarrollo de glaucoma en adultos atendidos en consulta externa en el Hospital Regional Isidro Ayora - Rodríguez Barros, Dionisio de Jesús (2015)
Glaucoma is an optic neuropathy characterized by progressive and irreversible development of morphological changes in the head of optic nerve and nerve fiber layer of the retina and functional changes with progressive reduction of the visual field. It determined risk factors involved in the development of glaucoma in patients from Outpatient of Isidro Ayora Regional Hospital, this research was descriptive, cross-sectional. It was conducted in the period from July 2014 to February 2015. The sample is consisted of 57 patients from the outpatient who had glaucoma and voluntarily agreed to participate in this study, which fulfill the inclusion and exclusion criteria. Data were recorded in a database of Microsoft Excel and analyzed using simple statistics. By applying the survey in the study group was obtained as result of the 57 patients with glaucoma, the majority was in a range of relevant age 56 and older. Predominantly female, most of these patients had open-angle glaucoma, as a whole were of mixed race, with much of these hypertensive patients, few hypothyroid patients and non-diabetic very high percentage. The collected information could be obtained that many of these patients to the study, risk factors outlined in this research work and also able to confirm the objectives. They were identified as age, race, gender, type of glaucoma and associated pathologies. Keywords: Glaucoma, Risk Factors.